Communication Patterns of Parents in Educating Children About Gadget Use in Bekasi - Noviari Yolania; Ummanah Ummanah (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study examines parental communication patterns in guiding children’s gadget use and identifies the challenges that arise in everyday parenting practices in Satriamekar Village, North Tambun District, Bekasi Regency. The research adopts a constructivist paradigm with a qualitative descriptive phenomenological approach. Data were collected through observation, in-depth interviews, and documentation involving three parents, three children aged 7–16 years who actively use digital devices, and one psychologist as a supporting informant. Data analysis followed the interactive model of Miles and Huberman, while credibility was ensured through source and method triangulation, member checking, and peer debriefing. The findings reveal three dominant communication patterns: (1) authoritarian, characterized by unilateral instructions and strict control; (2) permissive, marked by broad freedom with minimal supervision; and (3) authoritative or democratic, which combines clear boundaries with dialogue and mutual agreement. Among these, the authoritative pattern most effectively fosters children’s awareness of digital risks, acceptance of rules, and self-regulation in gadget use. The study also identifies key obstacles, including limited parental time, low digital literacy, inconsistent rule enforcement, peer pressure, pervasive digital culture, and communication tensions within the family.